2020
DOI: 10.1007/s40121-020-00376-5
|View full text |Cite
|
Sign up to set email alerts
|

Virus Coinfection is a Predictor of Radiologically Confirmed Pneumonia in Children with Bordetella pertussis Infection

Abstract: Introduction This study aimed to prospectively investigate the burden of pertussis in southeast Chinese children hospitalized with lower respiratory tract infection (LRTI) during a pertussis outbreak and to compare the outcomes of Bordetella pertussis infection with or without virus coinfections. Methods Children < 24 months of age hospitalized with LRTI were prospectively enrolled from January 2017 to December 2019. Demographic and clinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For instance, Esper and co-authors reported that influenza patients co-infected with rhinovirus tended to have milder disease [ 27 ]. On the other hand, co-infection of rhinovirus might be associated with refractory M. pneumoniae pneumonia and a higher frequency of B. pertussis LRT infection among hospitalized children [ 28 , 29 ]. Furthermore, concomitant infection of M. pneumoniae or parainfluenza virus 4 in COVID-19 patients was associated with worse clinical outcomes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Esper and co-authors reported that influenza patients co-infected with rhinovirus tended to have milder disease [ 27 ]. On the other hand, co-infection of rhinovirus might be associated with refractory M. pneumoniae pneumonia and a higher frequency of B. pertussis LRT infection among hospitalized children [ 28 , 29 ]. Furthermore, concomitant infection of M. pneumoniae or parainfluenza virus 4 in COVID-19 patients was associated with worse clinical outcomes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differently, in our case a co-infection with Rhinovirus/Enterovirus and Staphylococcus epidermidis was also observed. On one side, this coinfection might have played a role in the clinical complication; nevertheless, several studies have shown so far only positive associations between B. pertussis with co-infection and pneumonia, but not with severe disease and outcome [7,8]. Patients with severe clinical situation broad-spectrum antibiotic therapy (prior to any specific diagnosis) should consider drugs that can also control Bordetella.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, evidence confirms the presence of coinfections between B. pertussis and other pathogens, particularly viruses, although the impact of these on clinical outcome remains unclear. Some studies have observed a positive association between B. pertussis with viral co-infection and the development of pneumonia, but not with severe disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This is a novel report explaining such associations. Several other studies (9,14,15,18,(20)(21)(22) assessed the influence of B. pertussis on acute bronchiolitis, but they could not exclude the possibility of other respiratory pathogens contributing to the illness. In the present study, the leukocyte count was higher in patients with B. pertussisonly bronchiolitis infection than that in patients with RSVonly infection, MP-only infection, and infections with other pathogens (p < 0.008 for all comparisons), which could also help distinguish B. pertussis-associated acute bronchiolitis from other acute bronchiolitis etiologies.…”
Section: Discussionmentioning
confidence: 99%